2015
DOI: 10.1242/jeb.128926
|View full text |Cite
|
Sign up to set email alerts
|

Friends with benefits: the role of huddling in mixed groups of torpid and normothermic animals

Abstract: Huddling and torpor are widely used for minimizing heat loss by mammals. Despite the questionable energetic benefits from social heterothermy of mixed groups of warm normothermic and cold torpid individuals, the heterothermic Australian sugar glider (Petaurus breviceps) rests in such groups during the cold season. To unravel why they might do so, we examined torpor expression of two sugar glider groups of four individuals each in outside enclosures during winter. We observed 79 torpor bouts during 50 days of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
(65 reference statements)
0
16
0
Order By: Relevance
“…Communal roosting in birds can result in substantial rest-phase energy savings (Boix-Hinzen and Lovegrove 1998, McKechnie and Lovegrove 2001b, Wojciechowski et al 2011, Chappell et al 2016). However, communal roosting is by no means incompatible with torpor; Nowack and Geiser (2016) demonstrated that huddling in small mammals provides substantial energetic benefits when groups consist of torpid individuals or even a mix of torpid and normothermic individuals. Second, measurements of T a in unoccupied roost burrows overnight suggested that the interiors of the holes were approximately 6°C warmer than outside T a .…”
Section: Discussionmentioning
confidence: 99%
“…Communal roosting in birds can result in substantial rest-phase energy savings (Boix-Hinzen and Lovegrove 1998, McKechnie and Lovegrove 2001b, Wojciechowski et al 2011, Chappell et al 2016). However, communal roosting is by no means incompatible with torpor; Nowack and Geiser (2016) demonstrated that huddling in small mammals provides substantial energetic benefits when groups consist of torpid individuals or even a mix of torpid and normothermic individuals. Second, measurements of T a in unoccupied roost burrows overnight suggested that the interiors of the holes were approximately 6°C warmer than outside T a .…”
Section: Discussionmentioning
confidence: 99%
“…Animals were allowed to recover from surgery for three days before the start of experiments. Some of the collected data have been published previously in a different context (Nowack and Geiser, 2016), but in the current study we present new physiological and behavioral data with an emphasis on the response to fire cues.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, this species is gregarious, living in family groups throughout the year and individuals can decrease their resting metabolic rate via huddling (Fleming 1980). Interestingly, torpid and normothermic individuals are commonly found sharing one nest box, indicating that torpor use by one individual does not necessarily promote torpor use by other individuals in the same nest (Nowack and Geiser 2016). We hypothesized that exposing gliders to smoke and a charcoal-ash substrate, without a concomitant food reduction, will not induce torpor, as arboreal mammals are less likely to view a charcoal-ash substrate on the ground as a threat.…”
Section: Introductionmentioning
confidence: 99%
“…During multiday torpor in hibernators, the metabolic rate can be reduced to <5% of the basal MR and T b often falls to near 0°C, but substantial energy saving can also be achieved at relative high T b (Tøien et al, 2011 ; Ruf and Geiser, 2015 ). Huddling in groups could have further enhanced energy savings (Arnold, 1993 ; Gilbert et al, 2010 ; Eto et al, 2014 ; Nowack and Geiser, 2016 ). Although it is widely accepted that hibernating mammals can survive without food for about 6 months, recent data have shown that some can do even better than that.…”
Section: The Function Of Mammalian Heterothermy At the K-pg Boundarymentioning
confidence: 99%